Teacher Professional Competency Development at SD/MI Level - Dandi Irawan Sembiring; Muhammad Yusri; Ramadhan Syahputra; Amiruddin Siahaan; Amiruddin Amiruddin (Universitas Pahlawan Tuanku Tambusai, 2023)
The quality of a nation is largely determined by the quality of education. The process towards quality education requires professional educators in accordance with the code of ethics and the teaching profession. This study aims to analyze efforts to develop the competence of the teaching profession at the SD/MI level. This research uses a qualitative approach with the method of literature study. Sources of data and materials for analysis of the study use scientific literature relevant to the topic of discussion, including books, articles, seminar proceedings, and final assignments (thesis, dissertation). The data is obtained from credible sources such as Google Scholar and Sinta. The results of this study conclude that teacher competence is related to the authority to carry out their duties, in this case in using the field of study as learning material that acts as an educational tool, and pedagogical competence related to the teacher's function in paying attention to the behavior of students learning. Teacher competence is the result of a combination of abilities of many types, which can be in the form of a set of knowledge, skills and behaviors that must be possessed, internalized and mastered by teachers in carrying out their professional duties.